The beginning of African biblical interpretation: the Bible among the Batlhaping - G. West (Acta Theologica)
Prior to the translation of the Bible in Africa, Africans were already engaging with the Bible, initially as an iconic object of power and then as an aural object. In the first section of this article I attempt to detect elements of the early reception of the Bible among the BaTlhaping people. The second section of the article then analyses the theology that lies behind Bible translation, for rendering the Bible into local vernaculars is not a self-evident impulse. The translation of the Bible into local languages must be understood as an aspect of a larger theological project. Finally, the third section of the article reflects on the capacity of the Bible ‘to speak for itself’, arguing that once the Bible has been translated into a local language it slips, at least partially, out of the grasp of those who translated it.